2008
DOI: 10.1177/000348940811700710
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Impact of Thyroid Hormone Replacement on Objective Voice Parameters

Abstract: Thyroid hormone replacement therapy following total thyroidectomy has a measurable impact on mean fundamental frequency in female patients. The mechanism of this effect is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
2
11
1
1
Order By: Relevance
“…Results showed no significant difference between the two groups regarding register. These results agree with the results obtained by [18] that used a variety of methods to assess the vocal condition of patients with thyroid disease allowed for a more complete picture of the characteristics of a patient's voice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results showed no significant difference between the two groups regarding register. These results agree with the results obtained by [18] that used a variety of methods to assess the vocal condition of patients with thyroid disease allowed for a more complete picture of the characteristics of a patient's voice.…”
Section: Discussionsupporting
confidence: 89%
“…Results showed highly significant difference between the two groups regarding loudness with P-value (0.001) showed that one third (10/30) of patients with excessively soft loudness. These results agree with [4] they found that One-third of their patients presented with excessively soft loudness before surgery, also these results agree with [18,19] They found that patients with thyroid dysfunction had excessively soft loudness. The changes in voice loudness explained by [3] that proved that hyperthyroidism changes affect voice stability and loudness.…”
Section: Discussionsupporting
confidence: 85%
“…Tiroid hormon replasmanının hipotiroidisi olan hastalarda ses karakteristiklerini olumlu yönde değiştirdiği saptanmıştır. [9] Hipotiroidideki ses karakteristiklerinde değişikliklere neden olan patofizyolojik mekanizmalar tartışmalıdır ve ortaya konabilen kesin bulgular yoktur. Öne sürülen olası mekanizmalardan bazıları; hipotiroidide vokal kordlarda miksomatöz materyalin birikimi, krikotiroid kasta ödem ve vagus sinirinin ambiguous çekirdeğinde ödem gelişimidir.…”
Section: Discussionunclassified
“…Injury of the vocal folds induced by tracheal intubation was ruled out. Birkent et al 11 reported that thyroid hormone replacement therapy after total thyroidectomy had a measurable impact on mean frequency in female patients (increased from 223.48 to 237.64 Hz), but the mechanism of the effect was unknown. In our study, the thyroid function (T3, T4, TSH) was normal before operation, 1 week, 1 month, and 3 months after surgery in all patients, and it did not change significantly from the function observed before the operation.…”
Section: Discussionmentioning
confidence: 99%